The mortgage-backed security - Sánchez-Palacios Paiva, Manuel (2007)
The article begins with the legislative antecedents of the disappeared System of Saving and Mortgage Loans, formed by the «Mutuales de Vivienda» and its central organism «Banco de la Vivienda». Further explains the nature of the mortgage in our legislation and its accessory character, followed by the independent mortgage of the Germanic Law, whose nature examines, and develops the concept of the Negotiable mortgage and its market